Social integration of migrant workers and other ethnic minorities : a documentation of current research - Herfurth, Matthias; Hogeweg-de Haart, H. P. (Pergamon Press, 1982)
Social Integration of Migrant Workers and Other Ethnic Minorities: A Documentation of Current Research is a documentation of descriptions of completed social science research projects. The projects are organized based on the division of contents. Within the individual items of the division, the projects are sorted out alphabetically according to countries, within the countries themselves according to the seat of the research institution. This book will be of great interest to various individuals who need references regarding the various social science research projects.